Analysis of gelatin adulteration in edible bird’s nest using fourier transform infrared (FTIR) spectroscopy - Jamaluddin, Nurul Hidayah; Tukiran, Nur Azira (International Institute for Halal research and Training (INHART), International Islamic University Malaysia (IIUM) In collaboration with: Halal Institute, Prince of Songkla University, 2018)
Fraudulent incorporation of cheaper materials such as porcine gelatin into edible bird’s nest (EBN) can become a problem for reasons related to religious, allergy, ethical, and legal requirement. Thus, the present study aimed to detect porcine gelatin in the processed EBNs by using a combination method of Fourier transform infrared (FTIR) and chemometrics analysis, Principal Component Analysis (PCA). In the evaluation of the spiked samples, this method was able to detect at least 5% of porcine gelatin in EBNs. This method would be advantageous for quality control in the EBN industry.